AUDIT MANAJEMEN SUMBER DAYA MANUSIA, MOTIVASI KERJA, DAN GAYA KEPEMIMPINAN PADA KINERJA KARYAWAN DI RUMAH SAKIT AURA SYIFA KEDIRI - Setiyaningati, Mela Dwi Astari; Solikah, Mar’atus; Linawati, Linawati (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose off this study was to determine the effectt of HRM audit, work motivationn, and Ieadership styIe on empIoyee performance. IThis study usesi a quantitative approach too examine the reIationship between two factors. The causal associative method was used to determine the cause of the reIationship. The research sample amounted to 40 respondents and anaIyzed using multiple Iinear regressioni. The resuIts showed that HRM audit and leadership styIe had no effect oni employee performance, but work motivation partially affected employee performance. HRM audit, work rnotivation, and Ieadership styIe all affect empIoyee performance.